POLIETILENA GLIKOL (PEG) DALAM MEDIA IN VITRO MENYEBABKAN KONDISI CEKAMAN YANG MENGHAMBAT TUNAS KACANG TANAH (Arachis hypogaea L.) - Enni Suwarsi Rahayu; Edi Guhardja; Satriyas Ilyas; Sudarsono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
The objectives of this experiment were to determine response of epycotyl of nine peanut cultivars against polyethylene glycol (PEG 6000) induced stress under in vitro conditions, effective concentration of PEG to inhibit growth and development of epycotyl, evaluate tolerance of the cultivars against PEG stress, and evaluate changes in total proline content due to PEG stress. Growing epycotyls from peanut seeds (TDK) or from embryo axis (TTK) were planted on liquid MS-0 medium containing PEG 6000 (0%, 5%, 10%, 15%, and 20%). Growth, development, and the tissue damage score of the epycotyl were observed after six weeks. Total content of proline were analyzed for stressed and non stressed epycotyl to determine effect of PEG stress on proline accumulation. Results of the experiment indicated that addition of PEG 6000 in to MS-0 medium inhibited growth and development of peanut epycotyls and increased its total proline content. Addition of PEG 6000 might be used to simulate drought stress under in vitro condition. PEG at 15% concentration was effective for inhibiting growth and development of epycotyl explant. The response of peanut epycotyls against medium containing 15% PEG 6000 might be used as alternative methods for screening peanut tolerance against drought stress. The TDK and TTK might be used as explant, while increased in shoot length (TTK), in leaf number (TDK and TTK), in milted leaf number (TDK and TTK), in root number (TDK) and score of tissue damage (TDK) might be used as criteria for drought tolerance.